Elevated serine catabolism is associated with the heat shock response in Escherichia coli. - Matthews, R G (1989)
The biochemical events associated with the heat shock response are not well understood in any organism, nor have the signals that initiate the induction of heat shock protein synthesis been identified. In this work, we demonstrate that the rate of serine catabolism of Escherichia coli cells grown in glucose minimal medium supplemented with serine is elevated three- to sevenfold when the growth temperature is shifted from 37 to 44 degrees C. Elevations in growth temperature and mutations or treatments that lead to elevated basal rates of serine catabolism at 37 degrees C result in the excretion into the culture medium of acetate derived from exogenous serine. Increases in the basal level of serine catabolism at 37 degrees C do not per se induce a heat shock response but are associated with abnormalities in the pattern of induction of heat shock polypeptides following a temperature shift. We postulate that the events responsible for or resulting from the elevation in serine catabolism associated with a shift-up in temperature modulate the induction of 3 of the 17 heat shock polypeptides identified in E. coli. These observations suggest that heat shock diverts serine away from the production of glycine and C1 units, which are required for initiation of protein synthesis and for nucleotide biosynthesis, and towards acetyl coenzyme A and acetate.